Sorption mechanism and distribution of cadmium by different microbial species. (1st May 2019) - Li, Jie; Liu, Yu-Rong; Zhang, Li-Mei; He, Ji-Zheng
Abstract: Bioremediation programs of cadmium (Cd) by microorganisms have being proposed, but the underlying mechanism of the remediation ion remains unexplored. Here, the sorption efficiency and subcellular fraction distribution of Cd in three selected microbial species were investigated. Our results showed that both species of the microorganisms and initial Cd concentrations strongly affected the Cd sorption capacity. In the three microbial species, the Cd removal efficiency increased with decreased Cd concentrations. Specifically, Hansenula anomala removed the highest Cd ions in low concentration of 0.05 mg L −1 ; while in medium concentration of 0.5 mg L −1 and high concentration of 5 mg L −1, Bacillus subtilis removed the highest Cd ions. The subcellular fractionation allocation showed that Cd was mainly allocated on cell wall (mantle and inner wall) in Pseudomonas stutzeri and B. subtilis, while cell cytomembrane accumulated similar amount of Cd compared to the cell wall of H. anomala at concentration of 0.5 mg L −1 . Meanwhile, the Cd distributions on cell subcellular fractionation of the three species changed along the contact times, suggesting varied migration models during the biosorption process. Moreover, the functional groups involved in biosorption differed among the species based on Fourier Transform Infrared (FTIR) analysis. Our results have important implications for developing and improving Cd remediation by microorganisms, which is a low-cost and environmentally friendly bioremediation strategy of Cd pollution in environments. Graphical abstract: Image 1 Highlights: Species identity and Cd concentrations affected the Cd sorption capacity. Cd was mainly allocated on cell wall in P. stutzeri and B. subtilis . Cd allocated on both cell wall and cytomembrane in H. anomala . The three species showed various migration models during biosorption process.